Tanna's owl - Qitsualik-Tinsley, Rachel, 1953-; Qitsualik-Tinsley, Sean, 1969- (Inhabit Media Inc., 2019)
"When Tanna's father brings home an abandoned owl, she is not eager to take care of the needy, ugly little bird. Tanna must wake at 4:00 AM to catch food for the owl. She must feed it, clean up after it, all while avoiding its sharp, chomping beak and big, stomping talons. After weeks of following her father's instructions on how to care for the owl, Tanna must leave home for school. Her owl has grown. It has lost its grey baby feathers and is beginning to sprout a beautiful adult snowy owl coat. As she says good-bye to the owl, he is relieved not to have to care for it anymore, but also a bit sad. This heartwarming story based on the author's own life experience teaches young readers the value of hard work, helping, and caring--even when the thing you are caring for does not love you back."--